SCHOOL DIGITAL TRANSFORMATION MANAGEMENT IN THE HYBRID LEARNING ERA - Nababan, Juandi; Panjaitan, Binur (Smart Education, 2025)
Abstrak: The development of educational technology requires schools to carry out digital transformation to support hybrid learning that integrates face-to-face and online learning. This research aims to analyze the digital transformation management process in schools through a descriptive qualitative approach. The research focus includes digital planning, implementation of technology infrastructure, developing teacher competencies, as well as school leadership strategies in managing change. Data was obtained through literature study, document observation, and interviews from previous relevant research. The study results show that effective digital transformation requires digital strategy planning, infrastructure readiness, digital literacy of educators, adaptive school culture, and visionary leadership. Digital transformation is not just the provision of devices, but also a change in school management paradigm. This research provides implications for policy makers and school leaders in managing digital transformation sustainably in the hybrid learning era. Keywords: digital transformation, education management, hybrid learning, digital leadership, educational technology. Abstract : Perkembangan teknologi pendidikan menuntut sekolah melakukan transformasi digital untuk menunjang pembelajaran hybrid yang mengintegrasikan tatap muka dan pembelajaran daring. Penelitian ini bertujuan menganalisis proses manajemen transformasi digital di sekolah melalui pendekatan kualitatif deskriptif. Fokus penelitian meliputi perencanaan digital, implementasi infrastruktur teknologi, pengembangan kompetensi guru, serta strategi kepemimpinan sekolah dalam mengelola perubahan. Data diperoleh melalui studi pustaka, observasi dokumen, dan wawancara dari penelitian-penelitian relevan sebelumnya. Hasil kajian menunjukkan bahwa transformasi digital yang efektif memerlukan perencanaan strategi digital, kesiapan infrastruktur, literasi digital pendidik, budaya sekolah adaptif, serta kepemimpinan visioner. Transformasi digital bukan hanya penyediaan perangkat, melainkan perubahan paradigma manajemen sekolah. Penelitian ini memberi implikasi bagi pengambil kebijakan dan pimpinan sekolah dalam mengelola transformasi digital secara berkelanjutan pada era pembelajaran hybrid. Kata kunci: transformasi digital, manajemen pendidikan, pembelajaran hybrid, kepemimpinan digital, teknologi pendidikan.